Perlindungan Hukum Terhadap Penyandang Disabilitas Sebagai Korban Kekerasan - Mutriady, Anto (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One of the areas of law that must be enforced is criminal law, because its existence is still recognized as a means capable of overcoming and preventing violations or crimes. Talking about criminal law, it cannot be separated from four main problems, namely the problem of the perpetrator, the problem of the act, the problem of punishment and the problem of the victim. Criminal law is also a means to provide legal protection for all citizens from all forms of ill-treatment, discrimination and violence. Children are the next generation of the Indonesian nation who have the right and obligation to participate in building the Indonesian state and nation. Children are also the capital of development that will maintain and defend and develop the results of national development. Given the important role of children in this country, children's rights are expressly regulated in law, that the state guarantees that every child has the right to survival, growth and development and has the right to protection from violence and discrimination. Child protection is an effort to create conditions where every child can exercise their rights and obligations. Child protection is a manifestation of justice in a society, thus legal protection must be attempted in various areas of state and community life. In community life, it can be seen that not everyone is born perfect, many are born with deficiencies which we often know as the term disabled or disabled.